Determinan Sosiodemografi dan Peran Ayah Terhadap Kejadian Stunting di Kabupaten Timur Tengah Selatan: Determinan Sosiodemografi dan Peran Ayah terhadap Kejadian Stunting di Kabupaten Timur Tengah Selatan - Sine, Juni Gressilda Louisa; Peni, Jane Austen; Nur, Astuti; Loaloka, Meirina S.; Kewa Niron, Maria F. Vinsensia D. P.; Mirah Adi, Anak Agung Ayu; Exposto, Levi Anatolia S. M.; Rosario Pacheco, Cipriano do (Amerta Nutrition, 2026)
Background: Stunting is a chronic nutritional problem that has a serious impact. The results of SSGI in 2021 the prevalence of stunting in East Nusa Tenggara was 24.4 percent. The highest stunting in South Central Timor District (TTS) was 48.3 percent. The causes of stunting are multifactorial; in addition to inadequate nutritional intake, sociodemographic factors and the role of fathers can affect parenting and susceptibility to infectious diseases. The determinants of stunting incidence in each region are different, including sociodemographics and parenting patterns. Objectives: This study aims to determine the risk factors for stunting according to sociodemographics and the role of fathers in the South Central Timor district. Methods: This research is a quantitative study with a Cross-Sectional Design. The number of samples used was 280 people with a purposive sampling technique based on the researcher's criteria. The research instrument used questionnaires and anthropometric measurements. The data collected included sociodemographic variables, data on child characteristics, and the role of fathers in preventing stunting. Data obtained from secondary data interviews, observations, and anthropometric measurements to measure the nutritional status of toddlers. Data analysis was carried out in stages; the results of bivariate analysis with a p-value below 0.25 were included in the multivariate analysis modeling of logistic regression tests. This study received ethical approval from the Ethics Committee of the Poltekkes Kemenkes Kupang No LB.02.03/1/0156/2024. Results: The results of the bivariate analysis showed a significant relationship between a history of infectious diseases, low birth weight <2500 grams, low exclusive breastfeeding, nutritional status of pregnant women with KEK, and the role of fathers with the incidence of stunting in Tobu Village and Noesiu Village. This is indicated by a p-value <0.05, while the results of the multivariate analysis showed that the nutritional status of pregnant women and exclusive breastfeeding had the greatest influence on the incidence of stunting. Conclusion: The biggest risk factors for stunting in this study were maternal nutritional status and low exclusive breastfeeding. Specific variables need to be added in further studies, including complete basic immunization, smoking behavior, and nutritional intake.